Healthcare professional behaviour: health impact, prevalence of evidence-based behaviours, correlates and interventions. - Patey, Andrea M.; Fontaine, Guillaume; Francis, Jillian J.; McCleary, Nicola; Presseau, Justin; Grimshaw, Jeremy M. (Psychology & Health, 2023)
Healthcare professional (HCP) behaviours are actions performed by individuals and teams for varying and often complex patient needs. However, gaps exist between evidence-informed care behaviours and the care provided. Implementation science seeks to develop generalizable principles and approaches to investigate and address care gaps, supporting HCP behaviour change while building a cumulative science. We highlight theory-informed approaches for defining HCP behaviour and investigating the prevalence of evidence-based care and known correlates and interventions to change professional practice. Behavioural sciences can be applied to develop implementation strategies to support HCP behaviour change and provide valid, reliable tools to evaluate these strategies. There are thousands of different behaviours performed by different HCPs across many contexts, requiring different implementation approaches. HCP behaviours can include activities related to promoting health and preventing illness, assessing and diagnosing illnesses, providing treatments, managing health conditions, managing the healthcare system and building therapeutic alliances. The key challenge is optimising behaviour change interventions that address barriers to and enablers of recommended practice. HCP behaviours may be determined by, but not limited to, Knowledge, Social influences, Intention, Emotions and Goals. Understanding HCP behaviour change is a critical to ensuring advances in health psychology are applied to maximize population health.